APPROACHES TO ESSENTIALLY FILLING THE «ECONOMIC SECURITY OF THE ENTERPRISE» CATEGORY (Development Service Industry Management, 2023)
The article analyzes the existing approaches to the essential content of the category «economic security of the enterprise» and proposes an improved systematization of them, highlighting aspects: system management of the enterprise, perspective management of the enterprise, preventive management of threats and risks, compensatory management of threats and risks. The transformation of the essence of the concept of «economic security of the enterprise», its features and key characteristics in the temporal dimension was also analyzed: 1st stage - before the emergence of the concept of Industry 4.0 (until 2011); 2 stage - after the emergence of the Industry 4.0 concept (2011) until the Covid-19 pandemic (2019); Stage 3 – after the emergence of the Covid-19 pandemic (2019) and before a full-scale russian invasion (2022); Stage 4 – after a full-scale russian invasion (2022). It was established that the generalized concept of «normal functioning» of the enterprise within the framework of its economic security is characteristic of the 1st stage; for the 2nd stage - selection among the most important corporate resources: personnel, information and technologies, equipment and equipment; for the 3rd stage - allocation of intellectual potential among the company's resources and emphasis on the marketing component of economic security; for the 4th stage - an emphasis on the marketing component of economic security in the successful market activity of enterprises in the conditions of European integration of Ukraine and on resistance and protection from destabilizing factors. It has been established that the economic security of the enterprise is a complex characteristic that reflects the state of the enterprise, which contributes to the stable and maximally effective functioning and development of the enterprise in the future to achieve business goals and increase the competitiveness of the enterprise in modern competitive conditions, security and reducing the impact of all types of potential of the enterprise from internal and external risks and threats in the face of global challenges.
Keywords: economic security of the enterprise; systematization of views; functional component; marketing component; risk